2005
DOI: 10.1128/aac.49.7.2816-2821.2005
|View full text |Cite
|
Sign up to set email alerts
|

Imipenem for Treatment of Tuberculosis in Mice and Humans

Abstract: Chemotherapy of tuberculosis caused by multiple-drug-resistant (MDR) strains is problematic because of choices limited to relatively inefficacious and toxic drugs. Some beta-lactam antibiotics are active against Mycobacterium tuberculosis in vitro. We investigated the efficacy of imipenem in a mouse model of tuberculosis and in humans with MDR tuberculosis. Mice infected with M. tuberculosis strain H37Rv were treated with isoniazid or imipenem. Residual organisms in lung and spleen and survival of imipenem-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 16 publications
2
84
0
Order By: Relevance
“…Initial mortality due to ARDS in our patient was averted possibly because of anti micro bacterial action of gentamicin [10], levofloxacin and imipenem [11]. Partial response of ARDS and miliary TB can only be explained by anti micro bacterial action of antibiotics, as she had no evidence of pyogenic infection.…”
Section: Introductionmentioning
confidence: 78%
“…Initial mortality due to ARDS in our patient was averted possibly because of anti micro bacterial action of gentamicin [10], levofloxacin and imipenem [11]. Partial response of ARDS and miliary TB can only be explained by anti micro bacterial action of antibiotics, as she had no evidence of pyogenic infection.…”
Section: Introductionmentioning
confidence: 78%
“…Encouraging results were also reported in animal models. Although less effective than the first-line anti-TB drug INH, imipenem significantly reduced M. tuberculosis counts in the lungs and spleens of infected mice (Chambers et al, 2005). As a result, imipenem doubled the survival rate of infected mice (35% mortality vs. 70%).…”
Section: Potentiation Of Lactams In Mycobacteriamentioning
confidence: 92%
“…While only a very few cases in which TB patients treated with lactams in conjunction with or without potentiators have been reported, the results were always promising. One study using imipenem alone in MDR-TB patients with poor predicted outcomes achieved a 70% cure rate (Chambers et al, 2005). Another study showed that treatment of TB patients with an amoxicillin/clavulanate combination significantly reduced M. tuberculosis counts with early bactericidal activity comparable to patients treated with the frontline drug INH (Chambers et al, 1998).…”
Section: Potentiation Of Lactams In Mycobacteriamentioning
confidence: 98%
“…For RR-TB, MDR-TB and XDR-TB patients, off-label uses will be inevitable. Several clinical off-label experiences demonstrated the efficacy, safety, and tolerability profile of some antibiotics prescribed for other infectious diseases [14,15]. Among them, the drug most frequently prescribed is the linezolid, which is originally an antibiotic to treat infection caused by Grampositive bacteria.…”
Section: Off-label Use Of Anti-tb Drugsmentioning
confidence: 99%